Two-component jet simulations. II. Combining analytical disk and stellar MHD outflow solutions - Matsakos, T.; Massaglia, S.; Trussoni, E.; Tsinganos, K.; Vlahakis, N.; Sauty, C.; Mignone, A. (Astronomy and Astrophysics, 2009)
Context: Theoretical arguments along with observational data of YSO jets suggest the presence of two steady components: a disk wind type outflow needed to explain the observed high mass loss rates and a stellar wind type outflow probably accounting for the observed stellar spin down. Each component's contribution depends on the intrinsic physical properties of the YSO-disk system and its evolutionary stage. Aims: The main goal of this paper is to understand some of the basic features of the evolution, interaction and co-existence of the two jet components over a parameter space and when time variability is enforced. Methods: Having studied separately the numerical evolution of each type of the complementary disk and stellar analytical wind solutions in Paper I of this series, we proceed here to mix together the two models inside the computational box. The evolution in time is performed with the PLUTO code, investigating the dynamics of the two-component jets, the modifications each solution undergoes and the potential steady state reached. Results: The co-evolution of the two components, indeed, results in final steady state configurations with the disk wind effectively collimating the inner stellar component. The final outcome stays close to the initial solutions, supporting the validity of the analytical studies. Moreover, a weak shock forms, disconnecting the launching region of both outflows with the propagation domain of the two-component jet. On the other hand, several cases are being investigated to identify the role of each two-component jet parameter. Time variability is not found to considerably affect the dynamics, thus making all the conclusions robust. However, the flow fluctuations generate shocks, whose large scale structures have a strong resemblance to observed YSO jet knots. Conclusions: Analytical disk and stellar solutions, even sub modified fast ones, provide a solid foundation to construct two-component jet models. Tuning their physical properties along with the two-component jet parameters allows a broad class of realistic scenarios to be addressed. The applied flow variability provides very promising perspectives for the comparison of the models with observations.
Keywords: Astrophysics - Astrophysics of Galaxies; ISM: jets and outflows; magnetohydrodynamics (MHD); methods: numerical; outflows; stars: formation; stars: pre-main sequence; stars: winds